The discrete roles of individual FOXO transcription factor family members in B-cell malignancies - Lees, Jamie; Hay, Jodie; Moles, Michael W.; Michie, Alison M. (Frontiers in Immunology, 2023)
Forkhead box (FOX) class O (FOXO) proteins are a dynamic family of transcription factors composed of four family members: FOXO1, FOXO3, FOXO4 and FOXO6. As context-dependent transcriptional activators and repressors, the FOXO family regulates diverse cellular processes including cell cycle arrest, apoptosis, metabolism, longevity and cell fate determination. A central pathway responsible for negative regulation of FOXO activity is the phosphatidylinositol-3-kinase (PI3K)-AKT signalling pathway, enabling cell survival and proliferation. FOXO family members can be further regulated by distinct kinases, both positively (e.g., JNK, AMPK) and negatively (e.g., ERK-MAPK, CDK2), with additional post-translational modifications further impacting on FOXO activity. Evidence has suggested that FOXOs behave as ‘bona fide’ tumour suppressors, through transcriptional programmes regulating several cellular behaviours including cell cycle arrest and apoptosis. However, an alternative paradigm has emerged which indicates that FOXOs operate as mediators of cellular homeostasis and/or resistance in both ‘normal’ and pathophysiological scenarios. Distinct FOXO family members fulfil discrete roles during normal B cell maturation and function, and it is now clear that FOXOs are aberrantly expressed and mutated in discrete B-cell malignancies. While active FOXO function is generally associated with disease suppression in chronic lymphocytic leukemia for example, FOXO expression is associated with disease progression in diffuse large B cell lymphoma, an observation also seen in other cancers. The opposing functions of the FOXO family drives the debate about the circumstances in which FOXOs favour or hinder disease progression, and whether targeting FOXO-mediated processes would be effective in the treatment of B-cell malignancies. Here, we discuss the disparate roles of FOXO family members in B lineage cells, the regulatory events that influence FOXO function focusing mainly on post-translational modifications, and consider the potential for future development of therapies that target FOXO activity.